The Relationship between Duration of Gadget Use with Nutritional Status in Adolescents - Ganis, Hendrika Yuniartin; Laga Nur, Marselinus; Riwu, Rut Rosina (Universitas Nusa Cendana, 2023)
Adolescents' nutritional status often changes because of growth and development, which causes height and weight changes. Adolescents' nutritional status change has a relationship with the duration of gadget use. This study aims to determine the relationship between the duration of gadget use and the nutritional status of adolescents at Labuan Bajo. This research is an analytical observational study with a cross-sectional design. The sample size is 60 people. Sampling was used stratified random sampling. Data were collected using a validated questionnaire and analyzed by chi-square. The result showed that among 60 respondents, the duration of gadget use was high (57%), and almost all the nutritional status was normal (88%). The chi-square and Fisher's analysis showed no relationship between the duration of gadget use and nutritional status (p-value=0.628). Paying more attention to adolescent screen time is necessary because there are few rules for using gadgets for teenagers by making the rules about time for using gadgets. It would help to make the nutritional status normal and stable.